The baroclinic response to wind in a multiarm multibasin reservoir. (7th October 2019) - Imam, Yehya E.; Laval, Bernard; Pieters, Roger; Lawrence, Gregory
Abstract: Field data, a three‐dimensional hydrodynamic numerical model, and modal decomposition were used to examine the baroclinic response to wind in two interconnected multiarm lakes, Knewstubb and Natalkuz Lakes (British Columbia, Canada). Similar to lakes of simpler geometry, the first‐vertical first‐horizontal mode (V1H1) of Knewstubb and Natalkuz Lakes was found to be the most energetic mode. This V1H1 dominance is attributed to similarity between the relatively uniform distributions of along‐thalweg wind and surface‐layer flow for the V1H1 mode. Two bathymetric features, the geometric constriction between Knewstubb and Natalkuz Lakes, and changes in thalweg orientation relative to the wind field act to create subbasins in which wind forcing causes local metalimnetic tilts. These subbasin scale tilts deepen the metalimnion at the downwind ends of the subbasins, raise the metalimnion at the upwind ends, and are superimposed on the lake‐wide V1H1 tilt. The metalimnetic tilts in the subbasins are attributed to higher horizontal modes that are equivalent to V1H1 modes of the subbasins. Because the thickness of the metalimnion is significant, the subbasin metalimnetic tilts occur with variations in the metalimnetic thickness along the subbasins; the metalimnion is compressed at the downwind end and expanded at the other end of each subbasin. This variability in thickness leads to metalimnetic intrusions following the relaxation of wind forcing. The findings of this study contribute to characterizing the baroclinic response to wind in lakes of complex bathymetry. In particular, this study helps in understanding the effect of bathymetric features on modal composition of the baroclinic response.